The Leveraging of Corporate America: A Long‐Run Perspective on Changes in Capital Structure. Issue 4 (December 2016) - Graham, John R.; Leary, Mark T.; Roberts, Michael R.
Abstract : In a study published recently in the Journal of Financial Economics, the authors of this article documented a substantial increase in the use of debt financing by U.S. companies over the past century. From 1920 until the mid‐1940s, the aggregate leverage of unregulated U.S. companies was low and stable, with the average debt‐to‐capital ratio staying within the narrow range of 10% to 15%. But during the next 25 years, the use of debt by U.S. companies more than doubled, rising to 35% of total capital. And since 1970, aggregate leverage has remained above 35%, peaking at 47% in 1992. Moreover, this pattern has been observed in companies of all sizes and operating in all unregulated sectors. Changes in the characteristics of U.S. public companies during this period provide little help in explaining the increase in corporate leverage. For example, the displacement of tangible by intangible assets in many sectors of the U.S. economy during the past 50 years would have led most economists to predict, holding all other things equal, a reduction rather than an increase in aggregate corporate leverage. Instead, according to the authors' findings, the main contributors to the increases in U.S. corporate leverage since the 1940s have been external changes, including increases in corporate income tax rates, the development of financial markets and intermediaries, and the reduction in government borrowing in the decades following World War II. The authors' analysis also identifies these last two changes—the development of financial markets, including the rise of institutional investors and shareholder activism, and the post‐War reduction in government debt—as having played the biggest roles in the leveraging of corporate America.